Cognitive outcomes of the at-home brain balance program - Jackson, Rebecca; Meng, Yue (Frontiers in Child and Adolescent Psychiatry, 2024)
Accessibility to developmental interventions for children and adolescents could be increased through virtual, at-home delivery of training programs. Virtual childhood training programs and their effects on cognitive outcomes have not been well studied. To that end, this study examined the effects of the at-home Brain Balance ® (BB) program on the cognitive task performance of children and adolescents with baseline developmental and attentional difficulties. The study included students with reported diagnosis of ADHD, autism, anxiety, sensory processing disorder, or dyslexia, and students with no reported diagnosis (aged 4-17 years). The at-home BB program is delivered through (1) a computer-based format utilizing multimodal program activities previously studied in-center (multisensory stimulation, gross motor, coordination, balance, and nutritional recommendations); and (2) the BB app (visual motor, auditory and visual processing, and rhythm and timing training)creating a comprehensive program experience delivered remotely. Cognitive performance was measured by six cognitive tasks from Creyos Health before and after 3 months of participation in the at-home BB program (N = 316) or in-center BB program (N = 4,232), compared to controls. Results showed that overall cognitive assessment scores (including attention, response inhibition, and working memory) improved after participation in either the at-home or the in-center program, compared to controls. Importantly, significant improvements over the controls were observed for two tasks involving attention and inhibitory control, in both programs. Further, two analyses support that the effects on cognitive performance from either delivery format, in-center or at home, are comparable in magnitude. This research: (1) presents new findings demonstrating improved cognitive performance after completing the at-home BB program; (2) replicates previous findings of cognitive improvements after completing the BB program; and (3) suggests that the cognitive effects of virtual at-home BB training are similar to those observed for in-center BB training. Overall, the results demonstrate the effectiveness of the at-home BB program in improving cognitive functioning in pediatric populations with preexisting developmental and attentional difficulties. Virtual delivery and ease of use, provide at-home programs the potential to reduce barriers of access to much-needed developmental and cognitive support, for individuals who may otherwise lack access to high-quality, evidence-based developmental programs.